Statínová myopatia--rarita, alebo realita? - Pella, D (Vnitrni lekarstvi, 2010)
Statins are the most effective drugs for reducing LDL-cholesterol and have strong evidence based medicine documented by significant reduction of cardiovascular events in wide variety of patients. Despite this fact, they are still underused in common clinical practice. Many physicians have expressed concern about potential adverse effects, particularly severe muscle toxicity, which is an impediment to appropriate statin use. The clinical symptoms of statin myopathy include myalgia or muscle weakness, tiredness, cramps and/or creatinkinase activity increases (CK). Because hypercholesterolaemia is usually asymptomatic, any unwanted effect of drug used for its management can undermine adherence. Therefore it is very important to evaluate myopathy magnitude, prompt and rational individual management, and if applicable, restart of lipid-lowering therapy as soon as possible with regard to its type, dose and concomitant treatment.
Keywords: Hydroxymethylglutaryl-CoA Reductase Inhibitors; statiny; rizikové faktory; Muscular Diseases; nemoci svalů; Humans; lidé; Risk Factors